Full genome analysis of enterovirus D‐68 strains circulating in Alberta, Canada. Issue 7 (22nd December 2015) - Pabbaraju, Kanti; Wong, Sallene; Drews, Steven J.; Tipples, Graham; Tellier, Raymond
Abstract : A widespread outbreak of enterovirus (EV)‐D68 that started in the summer of 2014 has been reported in the USA and Canada. During the course of this outbreak, EV‐D68 was identified as a possible cause of acute, unexplained severe respiratory illness and a temporal association was observed between acute flaccid paralysis with anterior myelitis and EV‐D68 detection in the upper respiratory tract. In this study, four nasopharyngeal samples collected from patients in Alberta, Canada with a laboratory diagnosis of EV‐D68 were used to determine the near full‐length genome sequence directly from the specimens. Phylogenetic analysis was performed to study the genotypes and pathogenesis of the circulating strains. Our results support the contention that mutations in the VP1 gene and other regions of the genome causing altered antigenicity, as well as lack of immunity in the younger population, may be responsible for the increased severe respiratory disease outbreaks of EV‐D68 worldwide. J. Med. Virol. 88:1194–1203, 2016 . © 2015 Wiley Periodicals, Inc.